2000
DOI: 10.1073/pnas.97.18.10083
|View full text |Cite
|
Sign up to set email alerts
|

The MITE familyHeartbreaker(Hbr): Molecular markers in maize

Abstract: Transposable elements are ubiquitous in plant genomes, where they frequently comprise the majority of genomic DNA. The maize genome, which is believed to be structurally representative of large plant genomes, contains single genes or small gene islands interspersed with much longer blocks of retrotransposons. Given this organization, it would be desirable to identify molecular markers preferentially located in genic regions. In this report, the features of a newly described family of miniature inverted repeat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
176
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(183 citation statements)
references
References 51 publications
5
176
0
2
Order By: Relevance
“…Instead, transposon display (TD) was used to provide a better estimate of copy number. TD is a modification of the amplified fragment-length polymorphism technique (17), where genomic DNA is digested, ligated to an adapter, and used as template for PCR with a labeled primer that anneals, in this case, near one end of mPing elements (11,18,19). All DNA fragments that are visualized on TD gels should have an adapter primer at one end and an mPing element at the other end.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, transposon display (TD) was used to provide a better estimate of copy number. TD is a modification of the amplified fragment-length polymorphism technique (17), where genomic DNA is digested, ligated to an adapter, and used as template for PCR with a labeled primer that anneals, in this case, near one end of mPing elements (11,18,19). All DNA fragments that are visualized on TD gels should have an adapter primer at one end and an mPing element at the other end.…”
Section: Resultsmentioning
confidence: 99%
“…mPing copy number was determined by TD and performed as described (18,19). Final annealing temperature for selective amplification was 58°C with the 33 Plabeled primer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of Stowaway elements present in the extensively sequenced rice genome revealed that they predominantly occur in the vicinity of potential gene sequences (Mao et al 2000). This makes the Stowaway elements attractive for designing molecular markers based on insertional or inter-MITE polymorphisms (Casa et al 2000;Chang et al 2001) that could be targeted into gene-rich euchromatic regions. Our findings suggest that this approach is also feasible in pea, as at least part of the identified elements are located near potential gene sequences.…”
Section: Discussionmentioning
confidence: 99%
“…TD 기술을 활용하여 MITE(Miniature Inverted-repeat Transposable Elements)라고 불리는 특이한 특성을 갖는 TE가 개발되었다 (Casa et al, 2000).…”
Section: Sscp(single Strand Conformation Polymorphism)unclassified